ANALISIS KEBUTUHAN MEDIA E-FLIP BOOK BERBASIS PBL PADA MATA PELAJARAN PPKN KELAS IV SEKOLAH DASAR - Azzahra, Fatimah; Angger Wardhani, Prayuningtyas; Usman, Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning media acts as a communication tool that connects interactions between teachers and students. The existence of learning media is very important because it provides various benefits for both parties, both teachers and students. The aims of this research are to: 1) explore the use of text-based media in PPKN learning in class IV; 2) obtain views from various perspectives and identify the obstacles faced by educators and students in PPKN learning; 3) design and develop learning media that can be applied in PPKN learning. The research subjects consisted of 2 teachers and 15 class IV students at SDIT Al Ghifari. This research uses a descriptive qualitative approach. Data collection was carried out through interview techniques, filling out questionnaires, and observation. The results of the needs questionnaire analysis show that grade 4 students at SDIT Al Ghifari need an interesting learning media, especially in PPKN subjects.